Thin films from chitosan-based ZnO and MoS2 composites with antifungal properties - Muhammad Iqbal Hidayat; Khoiriah Khoiriah; Hera Desvita; Reza Audina Putri; Putra Mardika; Angelia Heberina Ompusunggu; Asranudin Asranudin; Teguh Hari Sucipto (Results in Engineering)
The study aimed to examine the application of chitosan and utilized molybdenum disulfide and zinc oxide to enhance nanocomposite thin films (CS/MoS2/ZnO). The thin films exhibit a compact morphology with reduced hollowness. The size of ZnO is 56.09 nm. The CS/MoS2/ZnO film performed hydrophobic, mechanical, and antifungal properties. The resulting film has a water contact angle value of 91°. The film exhibited good mechanical properties, which is the tensile strength of 30.83 MPa, elongation at break of 12.7%, and Young modulus of 17.54 MPa. It has antifungal activity of 18.32 mm against Rhizopus sp. and 18.71 mm against Aspergillus niger. Effective preservation of red chili pepper was observed in a 20-day storage period, minimizing weight loss and absence of fungal growth. The CS/MoS2/ZnO thin film possesses significant potential for application in the food industry owing to its antifungal and biodegradable properties.